Does classroom diversity improve intergroup relations? Short- and long-term effects of classroom diversity for cross-ethnic friendships and anti-immigrant attitudes in adolescence. (December 2021) - Bohman, Andrea; Miklikowska, Marta
This study examined short- and long-term effects of ethnic classroom diversity for intergroup relations in adolescence. Using a five-year panel of Swedish majority youth ( M ageT1 = 13.40, M ageT5 = 17.30), we found only limited direct effects of classroom diversity on anti-immigrant attitudes. However, classroom diversity increased the likelihood of cross-ethnic friendships, which in turn was associated with lower levels of anti-immigrant attitudes. Moreover, we found that the effect of classroom diversity on friendships remained also after adolescents transitioned to new schools. The findings highlight the importance of longitudinal analyses and contribute to a deeper understanding of how intergroup relations develop during adolescence. It brings new insights related to the longevity of classroom effects and to cross-ethnic friendships' ability to mediate the diversity–attitudes relationship.